SIRTET: A SERIOUS GAME FOR REHABILITATION OF THE UPPER LIMB OF STROKE PATIENTS: UM JOGO SÉRIO PARA REABILITAÇÃO DO MEMBRO SUPERIOR DE PACIENTES COM ACIDENTE VASCULAR CEREBRAL - Nascimento, Andressa Queiróz do (2024)
Hemiparesis is the main clinical manifestation of stroke. Affection of the upper extremity results in significant functional deficits, reducing quality of life. Thus, an effective treatment is necessary to restore upper limb function. The study aimed to analyze the therapeutic effects of an exercise program using a Serious Game (SG) developed for the rehabilitation of hemiparetic stroke patients, in addition to comparing these effects with those obtained through conventional physiotherapy. This was a Randomized Clinical Trial involving 8 chronic patients, aged 59.9±8.8 years. The Experimental Group (EG) received upper limb treatment using the SIRTET SG, and the Control Group (CG) received conventional kinesiotherapy. The treatment consisted of 10 weeks with two weekly sessions (totaling 20 sessions). The following were assessed: spasticity, upper limb motor function, handgrip strength, functional independence, manual dexterity and quality of life. Both groups showed improvements, with the EG results being superior in the variables motor function of the upper limb and quality of life. Therefore, the use of SG was beneficial in treating patients, and the combined use of this resource with conventional physiotherapy is recommended.